2023
DOI: 10.1093/ijnp/pyad051
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prolactin, Oxytocin, and Homocysteine With the Clinical and Cognitive Features of a First Episode of Psychosis Over a 1-Year Follow-Up

Maria Hidalgo-Figueroa,
Alejandro Salazar,
Cristina Romero-López-Alberca
et al.

Abstract: Background The clinical debut of schizophrenia is frequently a first episode of psychosis (FEP). As such, there is considerable interest in identifying associations between biological markers and clinical or cognitive characteristics that help predict the progression and outcome of FEP patients. Previous studies showed that high prolactin, low oxytocin and high homocysteine are factors associated with FEP 6 months after diagnosis, at which point plasma levels were correlated with some clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…We found that CP equivalent was significantly associated with plasma Hcy levels and FA reduction in people with SZ, suggesting that antipsychotic medication may be associated with increased Hcy and WM dysconnectivity in SZ. Preceding studies reported inconsistent results on the effects of antipsychotics on plasma Hcy levels in people with SZ: increased 32 , decreased 13 , 33 , and unchanged 34 36 . Similarly, it remains unclear whether antipsychotics reduce FA values in SZ 37 41 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that CP equivalent was significantly associated with plasma Hcy levels and FA reduction in people with SZ, suggesting that antipsychotic medication may be associated with increased Hcy and WM dysconnectivity in SZ. Preceding studies reported inconsistent results on the effects of antipsychotics on plasma Hcy levels in people with SZ: increased 32 , decreased 13 , 33 , and unchanged 34 36 . Similarly, it remains unclear whether antipsychotics reduce FA values in SZ 37 41 .…”
Section: Discussionmentioning
confidence: 99%